Cytokine and immune response-associated transcriptome profiles in cattle infected with Theileria parva vaccine stocks - Sibeko-Matjila, K.P. (Kgomotso Penelope) (University of Pretoria, 2023)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2021.